PUBLIC OPINION ON THE IMAGE OF LEADERSHIP H. SUYATNO REGENT OF ROKAN HILIR DISTRICT (Community Study of Bangko Subdistrict Rokan Hilir Regency) - Riki Hamdani; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Leadership is the nature of a leader who has the power and strength to control and change things for the better, leadership has a purpose, namely as a means and means of driving / motivation, leadership also has a function as administration and top management in the process of its activities. H. Suyatno is the regional leader of Rokan Hilir Regency, this leader is a mandate that Suyatno must guard as well as possible as a leader. The leadership mandate must be able to change the previous situation for the better, with the strength and power of top management and administration that a leader can do what he wants to do, but what the leader does will be assessed by the people around him, this assessment can be in the form of verbal or nonverbal, which can be with language or accompanied by gestures, a person's judgment is also a form of opinion or idea regarding something concerned. For approximately 4 years, Suyatno has led the Rokan Hilir Regency, many controversial things have resulted in the emergence of public opinion or public assessment of his leadership, implementing a policy of honorary dismissals in large numbers, there is also news about Suyatno who is a drug user. Everything that happened in the leadership of Suyatno that caused the controversy would lead to different opinions. This study aims to determine the Public Opinion on the Leadership Image of Suyatno, the Regent of Rokan Hilir Regency, and also to find out what factors shape this public opinion.This study used a qualitative descriptive method based on primary and secondary data sources and used observation, interview, and documentation data collection techniques. The number of informants in this study was thirty people, and the determination of the informants used purposive sampling. The data analysis technique uses the interactive data analysis model of Miles and Huberman, where the data obtained is then processed to be reduced, presented to produce a general conclusion. The results of this study resulted in different opinions about the image of Suyatno's leadership, but what was more dominant was negative opinion with the number of opinions of twenty-four of the thirty target informants, who said Suyatno's leadership was not good, on the grounds that honorary dismissal had no solution for being dismissed. and inaccurate policies such as urban development that is being carried out, and has also been known as a drug user which has resulted in public disappointment so that there is bad opinion, the community is also of the opinion that leaders should be good role models. Several factors form an opinion, namely past experience, circulating information and organization, these three factors influence the formation of public opinion, people are disappointed and do not expect much more about Suyatno leadership which can be seen from people's negative perceptions and attitudes towards Suyatno Suyatno leadership.Keywords: Public Opinion, Image of Leadership